Investigating unilateral pleural effusions: the role of cytology. Issue 5 (8th November 2018) - Arnold, David T.; De Fonseka, Duneesha; Perry, Siobhan; Morley, Anna; Harvey, John E.; Medford, Andrew; Brett, Mary; Maskell, Nick A.
The vast majority of undiagnosed unilateral pleural effusions have fluid sent for cytological analysis. Despite widespread use, there is uncertainty about its sensitivity to diagnose malignant pleural effusions (MPEs). Our aim was to ascertain the utility of cytology using a large prospective cohort. Consecutive patients presenting with an undiagnosed unilateral pleural effusion were recruited to this UK-based study. All had pleural fluid sent for cytological analysis. Cytological sensitivity was based on the final diagnosis at 12 months, confirmed by two consultants. Over 8 years, 921 patients were recruited, of which 515 had a MPE. Overall sensitivity of fluid cytology to diagnose malignancy was 46% (95% CI 42–58%). There was variation in sensitivity depending on cancer primary, with mesothelioma (6%) and haematological malignancies (40%) being significantly lower than adenocarcinomas (79%). MPEs secondary to ovarian cancer had high pick-up rates (95%). In asbestos-exposed males with exudative effusions, the risk of MPE was 60%, but cytological sensitivity was 11%. This is the largest prospective study of pleural fluid cytology and informs discussions with patients about the likely requirement for investigations following thoracentesis. In patients presenting with a clinical suspicion of mesothelioma, cytological sensitivity is low, so more definitive investigations could be performed sooner. Largest prospective study investigating unilateral pleural effusions; the value of cytology depends on the primary site http://ow.ly/u7Fo30lOQPD